A three-dimensional ISPH-FVM coupling method for simulation of bubble rising in viscous stagnant liquid. (15th June 2023) - Xu, Yixiang; Yang, Gang; Hu, Dean
Abstract: The bubble rising problem has always been one of the research hotpots in the field of multiphase flow simulation due to the complex topological evolution of the phase interface. In this paper, an approach of coupling incompressible smoothed particle hydrodynamic (ISPH) and finite volume method (FVM) in three-dimensional space (abbreviated as 3D ISPH-FVM coupling method) is developed to simulate the bubble rising in viscous stagnant liquid. In the 3D ISPH-FVM coupling method, the coupling framework between the two numerical schemes is established through the information exchange at the overlapping regions. The effect of surface tension is evaluated by implementing the 3D continuum surface force model (CSF). To verify the interface capture accuracy of the 3D ISPH-FVM coupling method, several benchmark cases are tested. Then, the single bubble rising in viscous fluid is simulated by 3D ISPH-FVM coupling method, in which the results are compared with the experimental data and other numerical results in the literatures. To further explore the ability of 3D ISPH-FVM coupling method in bubble rising simulation, the effect of some parameters (including numerical and physical parameters) on single bubble rising is investigated. Afterwards, the dynamics phenomena of two bubbles coalescence are also studied. Numerical results validate the robustness and stability of the present coupling model in simulating the bubble rising. Graphical abstract: Image 1 Highlights: A 3D ISPH-FVM coupling method is developed by taking the advantages of ISPH and FVM. The present method is convenient in tracking and capturing 3D flow interfaces. The stability and accuracy of the present method are verified by several benchmark tests. The complex 3D interface deformation of bubble rising motion can be well reproduced. The influence of numerical parameters on bubble rising is investigated.